NAFLD and HBV interplay - related mechanisms underlying liver disease progression - Tourkochristou, Evanthia; Assimakopoulos, Stelios F.; Thomopoulos, Konstantinos; Marangos, Markos; Triantos, Christos (Frontiers in Immunology, 2022)
Non-alcoholic fatty liver disease (NAFLD) and Hepatitis B virus infection (HBV) constitute common chronic liver diseases with worldwide distribution. NAFLD burden is expected to grow in the coming decade, especially in western countries, considering the increased incidence of diabetes and obesity. Despite the organized HBV vaccinations and use of anti-viral therapies globally, HBV infection remains endemic and challenging public health issue. As both NAFLD and HBV have been associated with the development of progressive fibrosis, cirrhosis and hepatocellular carcinoma (HCC), the co-occurrence of both diseases has gained great research and clinical interest. The causative relationship between NAFLD and HBV infection has not been elucidated so far. Dysregulated fatty acid metabolism and lipotoxicity in NAFLD disease seems to initiate activation of signaling pathways that enhance pro-inflammatory responses and disrupt hepatocyte cell homeostasis, promoting progression of NAFLD disease to NASH, fibrosis and HCC and can affect HBV replication and immune encountering of HBV virus, which may further have impact on liver disease progression. Chronic HBV infection is suggested to have an influence on metabolic changes, which could lead to NAFLD development and the HBV-induced inflammatory responses and molecular pathways may constitute an aggravating factor in hepatic steatosis development. The observed altered immune homeostasis in both HBV infection and NAFLD could be associated with progression to HCC development. Elucidation of the possible mechanisms beyond HBV chronic infection and NAFLD diseases, which could lead to advanced liver disease or increase the risk for severe complications, in the case of HBV-NAFLD co-existence is of high clinical significance in the context of designing effective therapeutic targets.